Iron-Sulfur Cluster Biogenesis in Chloroplasts. Involvement of the Scaffold Protein CpIscA - Abdel-Ghany, Salah E. (American Society of Plant Biologists, 2005)
The chloroplast contains many iron (Fe)-sulfur (S) proteins for the processes of photosynthesis and nitrogen and S assimilation. Although isolated chloroplasts are known to be able to synthesize their own Fe-S clusters, the machinery involved is largely unknown. Recently, a cysteine desulfurase was reported in Arabidopsis (Arabidopsis thaliana; AtCpNifS) that likely provides the S for Fe-S clusters. Here, we describe an additional putative component of the plastid Fe-S cluster assembly machinery in Arabidopsis: CpIscA, which has homology to bacterial IscA and SufA proteins that have a scaffold function during Fe-S cluster formation. CpIscA mRNA was shown to be expressed in all tissues tested, with higher expression level in green, photosynthetic tissues. The plastid localization of CpIscA was confirmed by green fluorescent protein fusions, in vitro import, and immunoblotting experiments. CpIscA was cloned and purified after expression in Escherichia coli. Addition of CpIscA significantly enhanced CpNifS-mediated in vitro reconstitution of the 2Fe-2S cluster in apo-ferredoxin. During incubation with CpNifS in a reconstitution mix, CpIscA was shown to acquire a transient Fe-S cluster. The Fe-S cluster could subsequently be transferred by CpIscA to apo-ferredoxin. We propose that the CpIscA protein serves as a scaffold in chloroplast Fe-S cluster assembly.